2008
DOI: 10.1007/s00268-008-9836-x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: Control and Loss of Control in Human Physiology and Disease

Abstract: Analysis of the human genome indicated that a large fraction of the genome sequences are RNAs that do not encode any proteins, also known as non-coding RNAs. MicroRNAs (miRNAs) are a group of small non-coding RNA molecules, with 20-22-nucleotide (nt) in length, and are predicted to control the activity of approximately 30% of all protein-coding genes in mammals. miRNAs play important roles in many diseases including cancer, cardiovascular disease, and immune disorders. The expression of miRNAs can be regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
130
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(139 citation statements)
references
References 175 publications
(286 reference statements)
0
130
0
9
Order By: Relevance
“…After binding to the RISC microRNAs regulate gene expression posttranscriptionally by a binding of specific mRNA, depending on the target mRNA they can function as oncogene or tumor suppressor. [10][11][12][13][14][15][16][17][18][19] Several microRNAs or miR-families involved in stem cell signaling are identified, for example, miR-21 involved in self-renewal and apoptosis, the let-7 family and miR-200 family involved in pluripotency and cell differentiation. 34 The miR-200 family is down-regulated in cells undergoing epithelial-to-mesenchymal transition (EMT).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After binding to the RISC microRNAs regulate gene expression posttranscriptionally by a binding of specific mRNA, depending on the target mRNA they can function as oncogene or tumor suppressor. [10][11][12][13][14][15][16][17][18][19] Several microRNAs or miR-families involved in stem cell signaling are identified, for example, miR-21 involved in self-renewal and apoptosis, the let-7 family and miR-200 family involved in pluripotency and cell differentiation. 34 The miR-200 family is down-regulated in cells undergoing epithelial-to-mesenchymal transition (EMT).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs regulate many genes known to play important roles in oncogenesis, angiogenesis and tissue differentiation. [10][11][12][13][14][15] In all, 1527 human microRNA sequences have been discovered to date and the number is increasing (miRBase. http:// www.mirbase.org, last accesses February 2012).…”
mentioning
confidence: 99%
“…Although miRNAs are able to negatively regulate the expression of target mRNAs, their expression is also regulated by different mechanisms such as specific translational regulation, methylation and histone deacetylation, DNA copy alteration and gene mutations affecting proteins involved in processing and maturation (Li et al, 2009a;Cummins and Velculescu, 2006). Furthermore, it has been reported that more than 50% of microRNA genes are often located in the fragile sites of chromosomes and in genomic regions which are prone to deletion, amplification and mutations (Corsini et al, 2012).…”
Section: Micrornas and Cancermentioning
confidence: 99%
“…Alternatively, tumor suppressor microRNA, called anti-oncomiRs, are able to inhibit tumor growth by targeting oncogenes (Corsini et al, 2012;Visone and Croce, 2009). For these reasons, oncomiRs are up- (Corsini et al, 2012;Li et al, 2009a). For this reason, currently have been identified 23 miRNAs (miR-1, miR-9, miR-15b, miR-130b, miR-16, miR-18a, miR-21, miR-34, miR-92a, miR-101, miR-122, miR-129-2, miR-132, miR-195, miR-199a, miR-221, miR-222, miR-223, miR-224, miR-375, miR-500, miR-675, miR-885-5p) detectable in peripheral blood and tissues, which are involved in hepatocellular carcinoma development and progression and we can name them HepatomiRNoma as a whole.…”
Section: Micrornas and Cancermentioning
confidence: 99%
“…In the recent years, a major attention in molecular biology research is devoted over various short and long non-coding RNAs [15]. Of the various subclasses of non-coding RNAs, microRNAs (miRNAs) are the most thoroughly characterized subclass of short RNAs in the recent literature [2].…”
Section: Introductionmentioning
confidence: 99%